IMAGES IN MEDICINEReal-time myocardial contrast echocardiography for echo-guided alcohol septal ablation - Veselka, Josef; Zemánek, David; Fiedler, Jiří; Šváb, Přemysl (Archives of Medical Science, 2009)
Alcohol septal ablation (ASA) for hypertrophic obstructive cardiomyopathy is performed through a percutaneous approach, in which 1-3 ml of absolute alcohol is introduced into the septal branch to create a controlled septal infarction of the basal interventricular septum with its subsequent shrinkage and outflow gradient elimination. During the procedure, contrast myocardial echocardiography is performed to delineate the area to be infarcted and to exclude contrast (and subsequently alcohol) injection in remote myocardial regions. We report for the first time the new possibility to use the real-time myocardial contrast echocardiography with low mechanical index for the better visualization of target septa area during ASA.